PENGELOLAAN ARSIP INAKTIF DI INTERNAL WAREHOUSE PT. SARI HUSADA I YOGYAKARTA - , INTAN SARI NURBAIDAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report dealing with inactive records management in Internal Warehouse of PT Sari Husada I Yogyakarta gives details on the practice of inactive records management conducted during PKL. The practice copes five stagesâsurvey, classification, description, filing, box-placement and labeling. There are three methods employed in the practice. The first method is observation and practice. It tries to examine the employeesâ daily activities associated with records and then directly practicing inactive records management. The second one is literature study applied to collect data from books or other texts related with inactive records. Lastly, interview is the last method used by proposing some questions about inactive records management to one in charge in IW inactive records. The result of PKL shows that inactive records management in IW is conducted well. This can be seen from the availability of records center, filing system, and scheduled records disposal. After all, it still lacks of human resources to perform the management routinely that it ends in poor inactive records arrangement.